154k views
13 votes
Solve by elimination:
9x+6y=18
-6x-6y=-24​

User Khozzy
by
5.5k points

2 Answers

4 votes

add these equations to eliminate y:

3x = -6

solve for x:

3x = -6. divide both sides by 3. x = -2

substitute x in the equation to find y:

9(-2) + 6y = 18.

6y - 18 = 18. add 18 to both sides.

6y = 36. divide both sides by 6. y = 6

end result:

x = -2

y = 6

User Jassa
by
5.8k points
14 votes

Answer:

1. x=−2/3 y+2

2. x=−y+4

Explanation:

1. 9x+6y=18

Step 1: Add -6y to both sides.

9x+6y+−6y=18+−6y

9x=−6y+18

Step 2: Divide both sides by 9.

9x/9=−6y+18/9

2. −6x−6y=−24

Step 1: Add 6y to both sides.

−6x−6y+6y=−24+6y

−6x=6y−24

Step 2: Divide both sides by -6.

−6x/−6 =6y−24/−6

User Ben Hoyt
by
5.8k points